Pengembangan Sistem Informasi Data Penduduk Desa Cengal - Hasan, Fujiyanto; Agita, Prissilia; Aditya, Dede; Hamonangan, Ryan (LPPM UNIKA Santo Thomas Medan, 2022)
Population data processing is a main activity carried out by the Government Section of Cengal Village, Maja District, Majalengka Regency on an ongoing basis. Where the current system often finds difficulties when searching for population data, duplication of data is found as a result of ordered population data collection and the occurrence of damage and data loss as a result of the existing storage media only in the form of documents. The purpose of this research is to design a population data processing application in Cengal village. The system development method used is the waterfall method with PHP and MYSQL scripts as database managers. This population data application is designed and built in order to help facilitate the search for population data and processing population data regarding births, deaths, immigrants and relocations, reducing the occurrence of damage and loss of population data due to storage media in the form of documents and can shorten operational time. With the storage media in the form of a good database, it can improve the performance of the government section in serving and presenting population information to the public so that it is better, faster and the application used can provide convenience to the user